Development of a sensitive and selective bioanalytical method of chebulinic acid by liquid chromatography‐electrospray tandem mass spectrometry and its pharmacokinetic application. Issue 2 (29th November 2022) - Verma, Sarvesh Kumar; Biswas, Arpon; Saxena, Shivani; Kumar, Mukesh; Mishra, Anjali; Choudhury, Abhijit Deb; Mishra, Tripti; Rais, Nisha; Narender, Tadigoppula; Bhatta, Rabi Sankar
Abstract: Chebulinic acid (CA), a polyphenolic compound extracted from the fruits of Terminalia chebula, has been recently reported as a novel neuraminidase inhibitor against the influenza A virus and also for various biological activities that require pharmacokinetic estimation. We report a proposed fragmentation pathway for the formation and selection of sodium and ammonium adducts using molecular thermodynamics. The chebulinic acid ammonium adduct was reproducible and stable compared to the earlier reported sodium adduct to quantify chebulinic acid by liquid chromatography‐tandem mass spectrometry. Chebulinic acid was extracted from plasma by protein precipitation followed by single‐step liquid‐liquid extraction by removing interfering metal adducts such as sodium. chebulinic acid resolution was achieved from the C18 column with mobile phase acetonitrile: methanol mixture and ammonium acetate buffer at a flow rate of 0.5 ml/min. The linear calibration curve ( r 2 ≥ 0.995) range was 3.52–1800 ng/ml. Finally, we report the oral pharmacokinetic profile of chebulinic acid in male Swiss albino mice plasma using the developed method.